Analisis Budaya Keselamatan Pasien terhadap Kepatuhan Penerapan SPO di Ruang Rawat Inap - Dalimunthe, Candra Rukmana; Girsang, Ermi; Ramadhani, Sri Lestari (Journal of Telenursing (JOTING), 2024)
This study analyzes patient safety and compliance with implementing SOPs in inpatient rooms. The research method used in this study is qualitative research with a phenomenological approach. The results of this study are that the manager's expectations and patient safety promotion actions have been implemented, organizational learning and improvements are evaluated in the form of online questionnaires, feedback, and communication about errors, and not all staff understand the procedures for reporting patient safety incidents, the openness of communication with superiors has been carried out well, and superiors provide positive reciprocal responses, there is no blaming response when reporting patient safety incidents from superiors or related parties, and the implementation of SOPs in the ward has not been carried out optimally and not all staff understand and implement them well. In conclusion, the implementation of SOPs on patient safety has been carried out well by all aspects of health workers in the hospital. Keywords: Patient Safety Culture, SOPs, Hospitals